Association of STAT6 genetic variants with childhood atopic dermatitis in Taiwanese population. Issue 3 (September 2015) - Lee, Yungling Leo; Yen, Jeffrey Jong-Young; Hsu, Li-Chung; Kuo, Nai-Wei; Su, Ming-Wei; Yang, Ming-Fong; Hsiao, Yu-Ping; Wang, I-Jen; Liu, Fu-Tong
Highlights We used HapMap Project data and TCHS cohort to compensate for the limitation of candidate-gene approach. We performed deep sequencing to identify novel variants around rs324011 in STAT6 gene and a total of seven variants were found, including rs167769. T allele of rs324011 increased the risk of childhood AD and haplotypes (rs167769/rs324011) was significantly associated with childhood AD in Taiwanese population. T alleles of both rs324011 and rs167769 would enhance STAT6 promoter activities in luciferase assay.